The Effect of Listening To Slow-Tempo Classical Music on Reading Comprehension in Students - Nadillah Aprilyani; Ahmad Arfandi; Ajeng Mutiara Anggita; Ratna Yunita Setiyani Subardjo (Journal of Psychology and Social Sciences, 2024)
Reading comprehension is a critical component of the learning process, particularly for students, as it is considered a fundamental skill that must be acquired. The current study utilizes the first movement of Beethoven's "Moonlight Sonata" as an experimental condition, given its slow-tempo properties. The primary aim of the study is to investigate the impact of slow-tempo classical music on the reading comprehension abilities of university students. A between-subject, randomized two-group design, post-test only research approach was utilized, with a total of 30 students participating in the study. The measurement of reading comprehension was conducted using the UTBK 2021 TPS test, with the experimental group taking the test while listening to Beethoven's "Moonlight Sonata," while the control group took the test without music. The study employs a two-tailed hypothesis and indicates that the Ha hypothesis is rejected. Therefore, it can be concluded that listening to classical music, specifically the "Moonlight Sonata 1st Movement" by Beethoven, does not have a significant effect on the reading comprehension abilities of students. However, it is recommended that students explore studying with and without music to determine their preferred method.